Role of color Doppler imaging in borderline size appendix-Simple method to improve specificity for appendicitis (International Journal of Scientific Research and Management (IJSRM), 2017)
Aims and objective: To differentiate between the normal appendix from inflamed appendix on color Doppler imaging. Continuous intramural vascular signal measuring at least 3mm on color Doppler imaging is highly specific for appendicitis in borderline-size appendix. Materials and method: Equipment and Method: All patients were scanned with a single ultrasound machine and 9–15-MHz transducers (GE Healthcare). Study design: Prospective study Sample size: 50 patients referred to radiology dept with possible appendicitis from 2015 to 2017. Source of the data: Patients coming to the department of radio diagnosis at SSIMS & RC Davangere with a clinical history of pain and tenderness in RIF and all patients who had undergone graded-compression sonography for possible appendicitis and whose appendices were of diagnostically borderline size (6–8 mm maximum outer diameter). Results: Of the 50 patients, 17had type 1 flow (of whom 3 had appendicitis); 13 had type 2 flow (of whom 11 had appendicitis); and 20had absent flow (of whom 5had appendicitis). Conclusion: Graded-compression US remains our first-line method in the evaluation of patients referred with clinically suspected acute appendicitis. Type II flow (Continuous linear or curvilinear flow >3mm) within the wall of the appendix is highly specific, yet insensitive, for appendicitis in borderline sized appendix. Type I flow (Punctuate dispersed signal) is neither sensitive nor specific for appendicitis and can be seen normal appendix.